The Effect of Rehabilitation Program on Lymphedema- related Arm Pain, and Volume after Mastectomy - Khoshnazr T. MSc; Mohammadi F. PhD; khankeh H. PhD; Haghighat Sh. MpH (Iran University of Medical Sciences, 2011)
Background ;aim: Upper extremity Lymph edema is the most common complication after mastectomy. The aim of this study is determining the effect of home based rehabilitation program on lymph edema related arm pain and arm volume after mastectomy among breast cancer survivors.   Material & Methods : In this quasi-experimental (before- after design), 16 post - mastectomy women with mild lymphedema (≤ 200 cc) referring to breast disease center affiliated with Jihad branch of Tehran University of Medical Sciences were selected by purposeful sampling. The interventions included educational program, arm exercises, self lymph drainage (SLD) by massage and compliance with risk reduction behaviors related to lymph edema at home during an 8 weeks program. Arm volume was measured by water displacement and pain was assessed by visual analog scale (VAS) before, one and two months after intervention. Study Participants were followed by call and in person in the clinic. Data was analyzed using repeated measurement.   Results: The findings showed a significant reduction in lymphedema volume (from 160 ±44 ml, to 35±23 ml) and pain (from 4.6, to .03) (p≤0/001).   Conclusion: Home based rehabilitation program reduces the volume of edema and intensity of pain after mastectomy. Evaluation of this method in patients with more edema volumes using control groups is recommended.